Hubungan Intensitas Waktu Bermain Gadget dengan Pencapaian Pembelajaran pada Peserta Didik Sekolah Dasar - Nadia Zahara; Zahwa Permata Islami; Adrias Adrias; Fadila Suciana (Politeknik Kampar, 2025)
With the rapid development of technology, gadgets have become an important part of everyday life, even for children who are still in elementary school. Excessive use of electronic devices, especially when playing, can affect students' learning habits and academic achievement. The purpose of this study was to determine the learning achievement results of elementary school students who are filled with the intensity of playing gadgets. This research method uses a descriptive qualitative approach, where data is obtained through a series of in-depth interviews conducted with teachers and parents of students. This study involved one of the elementary schools in Jorong Kampung Baru, West Pasaman Regency, with research subjects including parents, teachers and grade III students. The results showed that students who played too much electronic devices tended to experience decreased focus in learning, lack of participation and lower academic achievement compared to students who had better control over their electronic devices. In addition, it was found that parents and teachers should supervise children when using devices so as not to interfere with their academic achievement.